A peregrinação inventiva da viola de cocho : o limiar entre a tradição e o contemporâneo - Duarte, Sidnei Moura (2022)
The objective of the thesis is to investigate the paths taken by the viola de cocho, which was initially cataloged as a traditional instrument used in popular celebrations and parties, but which is currently present in concert halls, theaters, in shows both of regional music and rock, used in diverse musical formations that perform the most varied musical styles. It can be noted that, from the late 1970s to the mid-2010s, we find several studies that have as narratives identity constructions of a 'traditional' viola de cocho, which culminated in the registration of the viola as Brazilian intangible heritage in January 2005. Parallel to these recognition movements, there was the emergence of new situations of use of this instrument, inserting it in the last years a multiplicity of ways of doing and playing it. This thesis proposes to understand these practices, exploring new meanings, through a contemporary mapping that points out the trajectories taken, possible new practices and the use of the viola de cocho. In this pilgrimage, the viola de cocho has been adapting to new technologies – unusual woods, industrialized strings, electromagnetic pickups – and to different musical styles, such as the rock guitar or electric trough guitar and the concert viola. Based on studies carried out by researchers Julieta de Andrade (1981) and Abel Anjos Filho (1993), my experience as a researcher and guitarist for almost two decades and interviews with musicians and viola makers, I propose a map that exposes an understanding of regarding the works of the viola de cocho, translating its new meanings and, finally, proposing new notions for the understanding of this instrument.